Türkiye Futbol Federasyonu bünyesinde uyuşmazlık çözüm kurulu - Küçük, Dursun (My University, 2021)
Çalışmamızda, Türkiye Futbol Federasyonu (TFF) bünyesinde Uyuşmazlık Çözüm Kurulu (UÇK) incelenmiştir. TFF’nin ve UÇK’nın hukuki niteliğinin tartışılmış, TFF’nin kamu tüzel kişisi olduğu, 5894 sayılı yasada hukuk kurulu olarak tanımlanan UÇK’nın, yargı kurulu, tahkim heyeti, tahkim mahkemesi veya tüzel kişinin organı olarak nitelendirilebileceğini fakat mevzuat düzenlemesi ihtiyacını da vurgulayarak, TFF Hukuk Kurulları için, Avrupa İnsan Hakları Mahkemesinin (AİHM)‘‘yargı yeri/ mahkeme’’ tanımlaması, Anayasa Mahkemesinin (AYM) “yargı işlevi yerine getiren bir kurul” nitelendirmesini, mahkemelerin görevsizlik kararlarını ve Anayasa 59/ 3 hükmünü dikkate alarak, UÇK’nın “yargı organı görevi” yaptığı, sonucuna varılmıştır. Çalışmamızın devamında UÇK’nın mevzuatımıza giriş sürecinin kaynaklarda belirtildiğinin aksine FIFA (Federation Internationale de Football Association- Uluslararası Futbol Federasyonları Birliği) talimatınca gerçekleşmediğine değinilmiştir. FIFA’ya üye başkaca federasyonda, UÇK benzeri kurul bulunmamaktadır. Futbol ailesinin sözleşmeden doğan uyuşmazlıkların ülkelerin mevzuatları çerçevesinde, sporun yönetimine ve disiplinine ilişkin uyuşmazlıkların ise federasyon veya kurullarınca çözümlendiği, yabancılık unsuru taşıyanlarınsa mevzuatlarca sağlanan haklardan başka, tarafların özgürce seçmeleri kaydıyla FIFA DRC (Dispute Resolution Chamber -FIFA İhtilaf Çözüm Dairesi) ve CAS (The Court of Arbitration for Sport -Spor Tahkim Mahkemesi) nezdinde çözümlendiğine değinilmiştir. UÇK’nın geçmişten günümüze kurul oluşturulma ve görevine ilişkin süreçler incelenmiştir. AİHM, AYM, Kamu Denetçiliği Kurumu ve öğretide vurgulandığı üzere mevcut yapısıyla UÇK ve diğer TFF Hukuk Kurullarının, görünüşte tarafsız ve bağımsız olmadığı, adil yargılanma hakkını ihlal ettiği, kurulların oluşumunda çoğunlukla kulüp yönetimlerinin etkisi olduğu, buna karşın şikayetlerin çoğunlukla kulüplerden geldiği, AİHM kararları sonrası değiştirilmek zorunda kalınan TFF statüsüne rağmen sorunun çözülmediği kanısına varılmıştır. Çalışmamızda yasayla düzenlenmesi gereken görev, harç, vekalet ücreti, kurul oluşumu, UÇK üyelerinin nitelikleri, yargılama süreçleri, karar ve karara itiraz yolları, yargı yolu açıklığı gibi hususların talimatla düzenlenmesinin, yasaya ve hatta Anayasa’ya aykırı bir düzenleme olduğu sonucuna varılmıştır. Çalışmamızın son bölümünde UÇK ve Tahkim Kurulu kararlarının ilam niteliğinde olup olmadığını değerlendirilmiş, genel kanının aksine, kararların ilam mahiyetinde olduğunu kanısına varılarak UÇK’ya ilişkin çözüm önerilerimiz sunulmuştur.

The purpose of this dissertation is to examine the Dispute Resolution Committee (“DRC”) established within the Turkish Football Federation (“TFF”). In our study mainly the legal nature of TFF and DRC has been discussed and unltimately it has been concluded that TFF is a public legal entity whereas DRC, defined as a legal committee in the law numbered 5894, may be described as judicial board, arbitration committee, arbitration court or legal entity organ however considering the “judicial body” definition of European Court of Human Rights for TFF legal committees and the definition of the Turkish Constitutional Court as “the committee performing a judicial committee”, lack of jurisdiction decisions of the courts and also the Article 59/ 3 of the Constitution, we are of the opinion, that the ideal definition is that DRC performs the duty of a judicial organ by emphasizing the need of a legislative regulation in this field. In the following part of our study, it has been put forward that unlike publicly available sources, the legislation regarding DRC has not taken into effect according to the instruction made by FIFA (Federation Internationale de Football Association) and no similar committee exists in other FIFA member federations. Additionally, it has been mentioned that the contractual disputes of the football community are resolved within framework of the local legislation, the disputes with regards to the football management and discipline are resolved by the federation and its relevant committees, the disputes with the element of foreignness are resolved by FIFA Dispute Resolution Chamber and The Court of Arbitration for Sport based on the freewill of the parties, apart from the ways set forth in the legislation. The processes related to the formation and the duties of DRC have been examined. In line with the decisions of European Court of Human Rights, Turkish Constitutional Court, Ombudsman Institution and also the dominant opinion, we are of the opinion that DRC and other legal committees of TFF, are apperantly not objective and independent, violate the right to a fair trial due to their existing structures, since the DRC boards are formed under the influence of the clubs and this anomaly still exists despite of the recent amendment to the relevant Status of TFF following the decisions of European Court of Human Rights. In our study, it has been concluded that regulating matters such as competent authority, duties & fees, attorney’s fee, the formation of DRC, the qualification of its members, judgement process, right to appeal / objection through a directive (not through a law) is contrary to the law and even conflicting with the Constitution. In the final part of our study, it has been discussed whether the decisions of DRC and Board of Arbitration can be construed as court degree. Contrary to the popular opinion, we came to conclusion that a decision of abovementioned committees should be enforced like a court degree hence we came up with some recommendations with regards to DRC.
Keywords: Board of Arbitration; Civil law; Dispute Resolution Committee; Football Law; Futbol Hukuku; Medeni hukuk; Spor Hukuku; Tahkim Kurulu Sports Law; Turkish Football Federation; Türkiye Futbol Federasyonu; Uyuşmazlık Çözüm Kurulu